КОГНИТИВНЫЕ АСПЕКТЫ СЕМАНТИЧЕСКОЙ ДЕРИВАЦИИ ПРОИЗВОДНЫХ СЛОВ - Панахова, В. В. (Eurasian Journal of Philology Science and Education, 2015)
The paper aims to clarify the semantic, cognitive features of derivative words in English. The article analyses first the different points of views of distinguished linguists and summarizes their thoughts. The main characteristic feature of derivative words is its motivated character, the conditionality of its meaning with its initial unit. All the characteristic features of derivative words allow a person to form derivative lexical units in accordance with its pragmatic intention.